How to Select a Graduate School Program for a PhD in Biomedical Science. Issue 6 (23rd June 2022) - Lancaster, Carly L.; Higginson, Lauryn; Chen, Brandon; Encarnacion‐Rivera, Lucas; Morton, Derrick J.; Corbett, Anita H.
Abstract: The goal of this article is to provide guidance for those who have decided to apply to graduate school with the plan to obtain a PhD in biomedical science. Choosing an appropriate graduate school and program can seem like a daunting choice. There are numerous graduate training programs that offer excellent training with multiple specific program choices at any given institution. Thus, identifying a program that provides an optimal training environment, which aligns with the applicant's training and career goals, can be daunting. There is no single training program that is ideal for all applicants, and, fortunately, there is no sole perfect place for any individual applicant to obtain a PhD. This article presents points to consider at multiple phases of this process as collected from the authors, including a senior faculty member, a junior faculty member, and four current graduate students who all made different choices for their graduate training (Fig. 1). In Phase I of the process, the vast number of choices must be culled to a reasonable number of schools/programs for the initial application. This is one of the most challenging steps because the number of training programs is very large, and most applicants will rely primarily on information readily available on the internet. Phase II is the exciting stage of visiting the program for an interview where you can ask questions and get a feel for the place. Finally, Phase III suggests information to collect following the interview when comparing choices and making a final decision. While the process may feel long and can be stressful, the good news is that making informed decisions along the way should result in multiple options that can support excellent training and career development. © 2022 Wiley Periodicals LLC.